2018
DOI: 10.7150/jbji.26355
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity evaluation of chlorhexidine gluconate on human fibroblasts, myoblasts, and osteoblasts

Abstract: Introduction: Chlorhexidine gluconate (CHX) is widely used as a preoperative surgical skin-preparation solution and intra-wound irrigation agent, with excellent efficacy against wide variety of bacteria. The cytotoxic effect of CHX on local proliferating cells following orthopaedic procedures is largely undescribed. Our aim was to investigate the in vitro effects of CHX on primary fibroblasts, myoblasts, and osteoblasts.Methods: Cells were exposed to CHX dilutions (0%, 0.002%, 0.02%, 0.2%, and 2%) for either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 34 publications
6
90
2
5
Order By: Relevance
“…CHX has specific disadvantages because clinically used 2% CHX permanently halts cell migration and significantly reduces fibroblast, myoblast, and osteoblast survival in vitro. 42 Thus, further in vivo studies are required to examine and optimize CHX safety and efficacy.…”
Section: Antisepticsmentioning
confidence: 99%
“…CHX has specific disadvantages because clinically used 2% CHX permanently halts cell migration and significantly reduces fibroblast, myoblast, and osteoblast survival in vitro. 42 Thus, further in vivo studies are required to examine and optimize CHX safety and efficacy.…”
Section: Antisepticsmentioning
confidence: 99%
“…Altogether, these results suggest that CHX kill both tumoral and nontumoral control cells in the same way; altering their cell membrane permeability and damaging their genomic DNA lacking selectivity. Several early studies have been described as the cytotoxicity of CHX on different kinds of cells [13,33,38]. Previously, it was reported that 1% of CHX shows a cytotoxic effect on human gingival fibroblasts (same control cells used in our study) employing also MTT cell viability assays [39].…”
Section: Discussionmentioning
confidence: 62%
“…In conclusion, the results of this study show that the use of CHX considerably reduces P. gingivalis presence, peri-implant inflammation and improve the clinical outcomes of implant-supported restoration. Different in vitro studies showed how CHX was cytotoxic for fibroblast cells, myoblast, osteoblast, cell viability and migration [62]. However, its in vitro cytotoxicity is higher for concentrations close to 2%.…”
Section: Discussionmentioning
confidence: 99%